Utilization of temperature control technology to improve the quality of Assyifa Black Garlic at the Utsman bin Affan Islamic boarding school - Sebayang, Nur Ulina Warnisyah; Benny Hidayat; Raju (Jurnal Online Pertanian Tropik, 2024)
One alternative way to eliminate the distinctive properties of garlic is through processing, namely heat treatment which can improve the taste and create new qualities of garlic without removing the nutritional components of raw garlic, known as black garlic. However, several times there are often obstacles in fulfilling black garlic which can be produced on a large scale, does not require a long time, and is of high quality. Based on the considerations above, research was conducted on using temperature control technology to improve the quality of Asssyifa black garlic at the Utsman bin Affan Islamic boarding school. The equipment used is a thermolysis device with a capacity of 15 kg to 30 kg. This tool has a design similar to a cake-making oven but has a special rack and pan for garlic production. This research uses a survey method by looking directly at the physical characteristics of garlic processed into black garlic. Apart from that, this research also uses organoleptic tests to measure the quality of black garlic in terms of taste on the tongue. The research results, Black garlic Assyifa which is produced using a thermolysis device using the best temperature control is 70oC for 9 days, which has a predominantly sweet taste and a blackish color.